Gambaran Karakteristik Perilaku Bullying pada Anak SMP Kelas 1-2 di Sekolah Assa Addah Kota Bekasi - Ana Rizana; Rina Karlina M. Saleh (Universitas Malahayati, 2026)
ABSTRACT Bullying is a common problem throughout the world America (35 percent), Europe, Central Asia (32 percent), andIndonesia (21 percent), this shows that Indonesia is ranked 4th highest in the number of bullying cases that year. Based on data from the Indonesian Child Protection Commission (KPAI) in 2019, out of 161 cases reported to the school, 36 cases (22.4%) involved children who experienced bullying and violence, and 41 cases (25.5%) involved children who committed bullying and violence. To describe the picture of bullying behavior in junior high school students in grades 1-2 at the Assa'Addah Islamic School in Bekasi City in .. Research Method: the research method is a random sampling survey method and the number of respondents is 92 students. Results of the study, the gender is mostly male 55 people (59.8%), based on the age of the respondents, the majority are in the range of 14 years (64.1%) respondents, while based on the results of the history of bullying, 62% of respondents had been victims of bullying before attending Assa Addah Middle School in Bekasi City. physical bullying behavior as many as 35 respondents (38%) never experienced physical bullying, often experienced physical bullying as many as 29 respondents (31%), always experienced bullying as many as 20 respondents (22%), sometimes as many as 8 respondents (9%), and rarely 0%. Verbal bullying behavior as many as 37 respondents (40%) who never experienced verbal bullying, respondents who sometimes experienced verbal bullying as many as 28 respondents (27.1%), respondents who were often verbally bullied as many as 18 respondents (20%), rarely as many as 11 respondents (11.9%), and always experienced verbal bullying as many as 1 respondent (1%). Mental and psychological bullying as many as 38 respondents (41%) sometimes experience mental and psychological bullying, never experience bullying as many as 38 respondents (41%), often experience mental bullying as many as 17 respondents (19%), and respondents who rarely and often experience mental bullying none (0%). Cyber bullying behavior as many as 42 respondents (46%) stated that they had never experienced it, sometimes experience cyber bullying as many as 35 respondents (33%), often as many as 12 respondents (13%), always as many as 3 respondents (3%), and respondents who rarely experience cyber bullying none (0%). Keywords: Bullying Behavior, Physical Bullying, Verbal Bullying, Mental and Psychological Bullying, Cyber Bullying. ABSTRAK Bullying adalah masalah yang sering terjadi di seluruh dunia Amerika (35 persen), Eropa, Asia Tengah (32 persen), dan Indonesia (21 persen), ini menunjukkan bahwa Indonesia berada di urutan ke-4 tertinggi dalam jumlah kasus bullying pada tahun tersebut. Berdasarkan data Komisi Perlindungan Anak Indonesia (KPAI) tahun 2019 dari 161 kasus yangdilaporkan ke pihak sekolah, 36 kasus (22,4%) melibatkan anak yang mengalami bullying dan kekerasan, dan 41 kasus (25,5%) melibatkan anak yang melakukan bullying dan kekerasan. Mendeskripsikan gambaran perilaku bullying pada siswa SMP kelas 1-2 di sekolah Islam Assa'Addah Kota Bekasi tahun. Metode peneliian metode survey random sampling dan jumlah responden sebanyak 92 siswa. Hasil penelitian jenis kelamin terbanyak adalah laki laki 55 orang (59,8%),berdasarkan usia responden terbanyak berusia pada rentang 14 tahun (64,1%) responden, sedangkan berdasarkan hasil riwayat bullying sebanyak 62% responden pernah menjadi korban bullying sebelum bersekolah di SMP Assa Addah Kota Bekasi. Perilaku bullying fisik sebanyak 35 responden (38%) tidak pernah mengalami bullying fisik, sering mengalami bullying fisik sebanyak 29 responden (31%), selalu mengalami bullying sebanyak 20 responden (22%), kadang-kadang sebanyak 8 responden (9%), dan jarang 0%. Perilaku bullying verbal sebanyak 37 responden (40%) yang tidak pernah mengalami bullying verbal, responden yang kadang-kadang mengalami bullying verbal sebanyak 28 responden (27,1%), responden yang sering dibully secara verbal sebanyak 18 responden (20%), jarang sebanyak 11 responden (11,9%), dan selalu mengalami bully secara verbal sebanyak 1 responden (1%). bullying mental dan psikologis sebanyak 38 responden (41%) kadang-kadang mengalami bullying mental dan psikologis, tidak pernah mengalami bully sebanyak 38 responden (41%), sering mengalami bullying mental sebanyak 17 responden (19%), dan responden yang jarang dan sering mengalami bullying mental tidak ada (0%).perilaku cyber bullying sebanyak 42 responden (46%) menyatakan tidak pernah mengalami, kadang-kadang mengalami cyber bullying sebanyak 35 responden (33%), sering sebanyak 12 responden (13%), selalu sebanyak 3 responden (3%), dan responden yang jarang mengalami cyber bullying tidak ada (0%). Kata Kunci: Perilaku Bullying, Bullying fisik, Bullying Verbal, Bullying Mental dan Psikologis, Bullying Cyber.